2012
DOI: 10.1021/am2018223
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxygen Plasma Treatment on the Device Performance of Zinc Oxide Nanoparticle-Based Thin-Film Transistors

Abstract: Thin-films of zinc oxide nanoparticles were investigated by photoluminescence spectroscopy and a broad defect-related yellow-green emission was observed. Oxygen plasma treatment was applied in order to reduce the number of defects, and the emission intensity was quenched to 4% of the initial value. Thin-film transistors that incorporate the nanoparticles as active semiconducting layers show an improved device performance after oxygen plasma treatment. The maximum drain current and the charge carrier mobility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…Alternative, the high temperature annealing can be substituted by additional low temperature treatments such as UV irradiation, vacuum annealing, or plasma treatments, which anyway complicate the fabrication process. 195,242,243 Additionally, an active channel layer constituted by nanoparticles inherently features a high number of (grain) boundaries, each one acting as a potential barrier against charge transport. Furthermore, high film porosity and roughness at the interface semiconductor/gate dielectrics have been demonstrated to be detrimental for the TFT performance.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…Alternative, the high temperature annealing can be substituted by additional low temperature treatments such as UV irradiation, vacuum annealing, or plasma treatments, which anyway complicate the fabrication process. 195,242,243 Additionally, an active channel layer constituted by nanoparticles inherently features a high number of (grain) boundaries, each one acting as a potential barrier against charge transport. Furthermore, high film porosity and roughness at the interface semiconductor/gate dielectrics have been demonstrated to be detrimental for the TFT performance.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…23 It has been reported that the surface defect produces hydroxyl ions (OH -) when exposed to air. 24,25 In the current study the surface species and decrease in O vacancies caused a shift in the (002) diffraction peak to small 2θ values and reduced the c/a ratio. Decreases in O vacancies were also observed by the increased FWHM beyond 20 sccm.…”
mentioning
confidence: 55%
“…When exposed to air, surface O contents react with moisture in air to form hydroxyl ions (OH -). 24 It can thus be concluded that annealing in the Ar atmosphere and plasma oxidation caused a decrease in visible emission due to a reduction in O vacancies. In the Ar-annealed sample, the possibility of Zn interstitial defects increased, while O interstitials and Zn vacancies decreased as the annealing temperature was increased.…”
mentioning
confidence: 99%
“…It is a promising candidate for applications in optoelectronic devices as solar cells, field effect transistors, Schottky diodes or light-emitting diodes. [30][31][32][33][34] It has been shown recently that ZnO nanorods can be deposited into self-assembled dense thin films by standard methods like drop casting, spin coating or solvent evaporation from a vertically immersed substrate. 20,23,35 In dip coating structure formation is triggered by the interplay of convective assembly in the capillary regime and shear forces in the intermediate and viscous drag regime.…”
Section: Introductionmentioning
confidence: 99%